The Impact of Regulations Upon Accounting Theory (Book). - Burns, Thomas J.; Stone, Williard E. (The Accounting Review, 1980)
Abstract Reviews the book "The Impact of Regulations Upon Accounting Theory," edited by Barbara D. Merino.